Mobile communication experience of students in exchange programs between Indonesia and the Philippines - Wichitra Yasya; Titis Nurwulan Suciati; Gallen Ray Canillo; Rojean Patumbon; Chuking Pandia (Jurnal Kajian Komunikasi, 2022)
The use of technology and mobile communication became prevalent with the advent of the COVID-19 pandemic, where activities such as student exchange between two universities can be conducted virtually. Mobile communication, in this case, is related to communication using cellular devices based on computer technology, but also the characteristics of mobile communication itself, which is mobility or its ability to be used anywhere and at any time. The study aims to examine the lived experiences of mobile communication on undergoing student exchange programs between Indonesia and the Philippines. The study was conducted using the qualitative method with in-depth interviews as data collection. The research's informants are students from universities in Indonesia and the Philippines. Data were interpreted through a thematic analysis. The research found that mobile communication positively affected the students' learning and experience, mainly how it helps them continue their education despite being disrupted by the pandemic. However, poor connection, English skills, and language barriers affect their academic performance. Recommendations are put forward for further studies to focus on how the language barrier affected students' learning and behaviors on mobile communication. Another further study that can be done is to explore mobile communication through theories in virtual exchange. They are polymedia and affordance theories. Academic institutions should help and monitor students’ understandings that would help and allow the students to understand and learn more.